Panic Buying Perception in Walian Satu Sub-District, Tomohon City - Revno D. Turambi; Nikolas F. Wuryaningrat (AIBPM Publisher, 2020)
Currently the Covid-19 has infected many countries. Indonesia became one of the many countries that suffered the negative effects of the pandemic. Like other countries, this global pandemic health problem brings huge impacts on the economy. Thus, a study is needed to measure the perception of the people of Tomohon City especially South Tomohon regarding panic buying due to covid-19. This research was limited to the use of panic buying variable and the place of research is South Tomohon District especially Walian Satu area. This study made use of descriptive quantitative research in its methodology combined with qualitative interviews. The number of respondents in one-month data collection was 150 respondents. The result of this study were 89 respondents were indicated to still normally and rationally purchase basic necessities. However, 61 respondents have ever made unusual excessive purchases to anticipate the covid-19 pandemic.